Zuoqing granules attenuate ulcerative colitis via macrophage polarization modulation: involvement of the PPAR-γ/NF-κB/STAT1 signaling axis - Deng, Heng; Li, Ming; Fang, Xiaoli; Tang, Kun; Xu, Shuqing; Ding, Rui; Li, Zilong (Frontiers in Pharmacology, 2025)
BackgroundAlthough our prior clinical study demonstrated the efficacy of Zuoqing granules (ZQGs) in treating ulcerative colitis (UC), the underlying immunomodulatory mechanisms remained unclear. This study systematically investigated ZQG’s therapeutic effects through macrophage polarization modulation and related signaling pathways using both in vivo and in vitro models.MethodsIn vivo, dextran sulfate sodium (DSS)-induced UC rats were divided into normal control, DSS model, and ZQG treatment groups (high/medium/low doses). Colon tissues were analyzed using histopathology [hematoxylin and eosin (HE) staining], macrophage phenotyping (CD86+/CD206+ immunofluorescence and flow cytometry), signaling pathway assessment (PPAR-γ, NF-κB p65, p-NF-κB p65, and STAT1 through Western blot/qPCR), and cytokine profiling (TNF-α, IL-6, IL-10, IL-1β, and IL-4 using ELISA). In vitro, lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages were treated with ZQG-conditioned medium and a PPAR-γ antagonist (GW9662) to validate direct effects.ResultsZQG treatment dose-dependently (1) ameliorated colonic mucosal damage, reducing histological scores by 52% compared to that in the model group, (2) modulated macrophage polarization by increasing the M2 phenotype (CD206+ cells, 3.25-fold increase) while decreasing M1 macrophages (CD86+ cells, 70% reduction), (3) upregulated PPAR-γ expression (2.0-fold increase) while suppressing NF-κB activation (43% decrease in p-NF-κB) and STAT1 signaling (48% and 40% reductions in protein and mRNA levels, respectively), and (4) rebalanced inflammatory cytokines, with 55%–62% reductions in TNF-α, IL-6, and IL-1β and 185%–210% increases in IL-10 and IL-4. In vitro studies further confirmed that ZQG directly shifted macrophage polarization via PPAR-γ, inhibiting M1 polarization (an effect abolished by GW9662).ConclusionZQG ameliorates UC by modulating macrophage plasticity through the PPAR-γ/NF-κB/STAT1 axis, a mechanism validated in vitro as PPAR-γ-dependent. These findings elucidate its clinical efficacy and support its use as a multi-target UC therapy.